UPAYA MENINGKATKAN KETERAMPILAN BERKOMUNIKASI SISWA DENGAN TEMAN MENGGUNAKAN LAYANAN BIMBINGAN KELOMPOK DENGAN TEKNIK ROLE PLAYING - Siswanto, Nafisa Alva; Hidayati, Richma; Gudnanto, Gudnanto (Jurnal Muria Research Guidance and Counseling (MRGC), 2024)
The aim of this research is to determine the improvement of students' communication skills through group guidance services using role playing techniques. Communication skills: Communication is a speaking skill possessed by a person that can be used in verbal and nonverbal techniques that can be used to understand or resolve a conflict constructively.This type of research is quantitative research. The method used by researchers is Quasi Experimental research. The subjects of this research were class XI Mipa 5, totaling 16 students. which will be divided into 2 groups, namely the control group and the experimental group. The dependent variable in this research is improving students' communication skills, while the independent variable is group guidance services using role playing techniques.The results of this research indicate that before group guidance was carried out using the role playing technique (pretest), the condition of students' communication skills tended to be low with an average of 48.625 and after being given group guidance using the role playing technique (posttest), students' communication skills experienced a significant increase with an average of 62,375.From the results of the hypothesis test, it was found that there was a significant difference regarding students' communication skills before and after being given group guidance services using role playing techniques, with a significance of 0.012. Thus it can be concluded that implementing group guidance services using role playing techniques can improve students' communication skills.